The Role of Cultural Reservation Center (BPCB) Jambi In Preserving History Site: Situs Bukit Siguntang - Andi andi; Rudy Gunawan; Nadia Utami; Ainul Rizki; Hana Fatimah Azzahra (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2020)
Palembang is the oldest city in Indonesia, a historic city, and a city that is respected with the greatness of the glory of the Srivijaya kingdom. Various events have become important historical traces for the local and general public, one of the historical traces is historical sites. The many historic sites in Indonesia make the central government make laws about cultural heritage that must be preserved. One of the famous sites in Palembang is the Siguntang Hill Site. The management of the Bukit Siguntang Site is entered into the regional government and overseen by the BPCB. The purpose of this study was to determine the role of the BPCB Jambi on the Bukit Siguntang Site and the local government that included the community in the preservation of the Siguntang Hill Site. Data collected through a qualitative approach by exploring and interviewing participants accompanied by a review of various literature. The results of this study are that Jambi BPCB has a sufficient role especially in zoning the Bukit Siguntang Site area which is divided into three zones, namely: the core zone, the buffer zone, and the development zone. The regional government develops and utilizes the Siguntang Hill Site by building various supporting facilities to become historical attractions. The conclusion is that the BPCB Jambi has a role in preserving the Bukit Siguntang Site through supervision and monitoring as well as activities that involve collaboration with the local regional government.